Introducing multilingualism a social approach - Weber, Jean Jacques; Horner, Kristine (New York Routledge, 2018)
"Introducing Multilingualism is a comprehensive and user-friendly introduction to the dynamic field of multilingualism. Adopting a compelling social and critical approach and covering important social and educational issues, the authors expertly guide readers through the established theories, leading them to question dominant discourses on subjects such as integration, heritage and language testing. This second edition has been fully revised and updated, featuring new chapters on multilingualism in new media, the workplace and the family."--Provided by publisher.
Part I Theoretical and methodological considerations -- Part II Multilingualism within and across languages -- Part III Societal and individual multilingualism -- Part IV Multilingualism in education and other institutional sites -- Part V Critical analysis of discourse -- Part VI Further directions in the study of multilingualism -- Conclusion.
"First published by Routledge 2012"--Title page verso.
Includes index (pages 299-308)
Keywords: Multilingualism -- Social aspects; Languages in contact